Update on Dementia 2016
DOI: 10.5772/64693
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Study of Degenerative Protein Modifications in the Molecular Pathology of Neurodegeneration and Dementia

Abstract: Dementia is a major public health burden, and the World Health Organization has identified this disorder as a major public health priority. There are limited treatment options due to poor understanding of key mechanism of dementia pathogenesis. Dementia has been regarded as a proteinopathy in which alterations of brain protein structure and function are the key features of the disorder. Proteinopathy can be triggered by degenerative protein modifications (DPMs), misfolding, aggregation, and deposition of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The clinical and experimental studies concluded that cerebrovascular disease and hypoxic-ischemic brain injury are the primary causes of cognitive impairment and dementia [29]. The progressive cycle of hypoxic-ischemic brain injury induces protein misfolding, aggregation and DPMs, leading to cognitive decline and dementia [15]. Further, the changes and posttranslational modification of proteins in response to chronic sustained and intermittent forms of hypoxia have been reviewed by Kumar and Klein [102].…”
Section: Hypoxia-induced Dpms and Its Role In Aging And Neurodegeneramentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical and experimental studies concluded that cerebrovascular disease and hypoxic-ischemic brain injury are the primary causes of cognitive impairment and dementia [29]. The progressive cycle of hypoxic-ischemic brain injury induces protein misfolding, aggregation and DPMs, leading to cognitive decline and dementia [15]. Further, the changes and posttranslational modification of proteins in response to chronic sustained and intermittent forms of hypoxia have been reviewed by Kumar and Klein [102].…”
Section: Hypoxia-induced Dpms and Its Role In Aging And Neurodegeneramentioning
confidence: 99%
“…The proteins undergo alterations by spontaneous non-enzymatic Degenerative Protein Modifications (DPMs) including oxidation, deamidation, carbamylation, carbonylation, glycation etc. The DPMs change protein charge state, hydrophobicity and threedimensional structure that influence functional activities and induce aggregation [9][10][11][12][13][14][15]. These protein modifications and accumulation of modified proteins are allied to aging and the development of age-associated pathologies like neurodegenerative diseases [10,16].…”
mentioning
confidence: 99%